2017
DOI: 10.21162/pakjas/17.5994
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE EFFICACY OF PYRETHROIDS ON Aedes aegypti, Aedes albopictus AND Culex quinquefasciatus COLLECTED FROM DIFFERENT ECOLOGICAL ZONES OF PUNJAB, PAKISTAN

Abstract: Chemical control is widely adopted method in mosquito control that emphasizes on the management of the adult and larval populations using various insecticides. Present study was carried out in the year 2015 to use chemicals which were currently being utilized in mosquito control program against prevalent mosquito species (Culex and Aedes spp.) collected from different ecological zones of Punjab (Pakistan) (i.e. Faisalabad, Lahore and Rawalpindi) formed as a result of dengue prevalence to evaluate their efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…gambiae. The author of [42] evaluated the efficacy of different pyrethroid insecticides against some mosquito species. The results indicated that cypermethrin showed a more significant percent mortality, followed by lambda-cyhalothrin and deltamethrin.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae. The author of [42] evaluated the efficacy of different pyrethroid insecticides against some mosquito species. The results indicated that cypermethrin showed a more significant percent mortality, followed by lambda-cyhalothrin and deltamethrin.…”
Section: Discussionmentioning
confidence: 99%